2016
DOI: 10.1177/0091026015624714
|View full text |Cite
|
Sign up to set email alerts
|

Spurious or True? An Exploration of Antecedents and Simultaneity of Job Performance and Job Satisfaction Across the Sectors

Abstract: The purpose of this study is to test differences and similarities of the public, private, and nonprofit sector employees by examining the antecedents and simultaneity of job satisfaction and job performance. The results, assessed by seemingly unrelated regression, showed that job satisfaction positively affects job performance, or vice versa. Explanatory variables such as goal ambiguity, leader-member exchange, and so forth also exerted significant effects on the outcome variables across three sectors. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 93 publications
2
44
0
3
Order By: Relevance
“…Thus, job satisfaction represents individuals’ emotional state related to their work or work environment, resulting from positive or negative appraisal of their job or job experiences (Robbins & Judge, 2016). Job satisfaction has been suggested to be related to perceived fulfillment of one’s needs through work and of one’s job-related needs at work for teachers in schools (Hsieh, 2016; Hulpia et al, 2009).…”
Section: Theoretical Review and Hypothesesmentioning
confidence: 99%
“…Thus, job satisfaction represents individuals’ emotional state related to their work or work environment, resulting from positive or negative appraisal of their job or job experiences (Robbins & Judge, 2016). Job satisfaction has been suggested to be related to perceived fulfillment of one’s needs through work and of one’s job-related needs at work for teachers in schools (Hsieh, 2016; Hulpia et al, 2009).…”
Section: Theoretical Review and Hypothesesmentioning
confidence: 99%
“…Results showed that even in adverse workplace conditions, employees' performance can increase in presence of spiritual well-being (Tejeda, 2014). In another study, 27 employees/housekeepers of Latina Hotels were interviewed and results showed that all of them were exposed to workplace hazards and poor work conditions due to which employees were stressed and performance was affected (Hsieh, 2016). In Eskisehir, metal industry employees were surveyed and critical environmental conditions were investigated.…”
Section: Work Conditionsmentioning
confidence: 99%
“…Contar con empleados con alto cp equivale a garantizar relaciones interpersonales marcadas por la empatía, mayores niveles de compromiso en la realización de la tarea, menor cinismo hacia la organización y mayor afectividad positiva (Larson et al, 2013;Luthans & Youssef, 2013;Salessi & Omar, en prensa). Así, la organización se verá favorecida con desempeños de mayor calidad y miembros más involucrados, en tanto que los trabajadores experimentarán mayores niveles de satisfacción laboral (Alessandri, Borgogni, & Latham, 2017;Hsieh, 2016). Al mismo tiempo, se sugiere poner en marcha programas de entrenamiento en estrategias para responder eficazmente a las normas organizacionales en materia de expresión emocional e incrementar la inteligencia emocional de los empleados para lidiar con el estrés y la presión cotidiana.…”
Section: Limitaciones Fortalezas E Implicaciones Prácticas Del Estudiounclassified